Análise do comportamento das curvas de lactose e glicose sanguínea em militares do exército brasileiro durante o teste de 12 minutos - Ferraz Cantanhede, Luiz Alexandre (2005)
Regular physical exercise represents an important factor in reducing the indices of cardiovascular morbi-mortality. Wasserman and McLlory (1964) introduced the term threshold anaerobic as the intensity of exercise in which an exponential increase of blood lactate occurs. At present, the importance of the increase in levels of glucose is being researched. In this transversal study, 15 male brazilian soldiers were analyzed, between 22 and 41 years of age, who achieved the mark of "E" (excellent) in the 12 minute test, during the Physical Evaluation Test. Blood samples (digital pulp) were collected in five stages during the test (repose, 3, 9, 12 and 13 ¹/² minutes). The KS test was applied for normality of sample, the correlations of Pearson and Spearman and ANOVA one Way and Tukey were applied, as statistical procedures. The sample presented average lactate levels (mMol l-1) of 2.32 ± 0.73 ; 3.65 ± 1.08; 7.9 ± 3.05; 10.44 ± 5.14 and 7.12 ± 4.57. The levels of glucose (mg/dl) found were: 77.53 ± 13.11; 78.06± 12.73; 84.20 ± 16.93; 98.93± 25.49 and 142.46 ± 23.10. It can be inferred that a moderate correlation exists between the lactate and glucemic curves during the 12 minute test, principally after the anaerobic threshold is reached.